To transform the function \( f(x) = 7x \) according to the stated operations, we need to apply each transformation step by step.
-
Horizontal Stretch by a factor of 5: To horizontally stretch a function by a factor of \( k \), we replace \( x \) with \( \frac{x}{k} \). So, we replace \( x \) with \( \frac{x}{5} \): \[ f(x) = 7\left(\frac{x}{5}\right) = \frac{7x}{5} \]
-
Moved up 3 units: This is done by adding 3 to the function: \[ f(x) = \frac{7x}{5} + 3 \]
-
Reflected across the x-axis: To reflect the function across the x-axis, we multiply the entire function by -1: \[ f(x) = -\left(\frac{7x}{5} + 3\right) = -\frac{7x}{5} - 3 \]
So, the transformed function is: \[ f(x) = -\frac{7x}{5} - 3 \]
Let's analyze the options provided:
- \( \text{Option #1: } f(x)=-7^{5}x+3 \) → Incorrect
- \( \text{Option #2: } f(x)=-7^{1/5}x+3 \) → Incorrect
- \( \text{Option #3: } f(x)=\frac{1}{5}\cdot7^{-x}+3 \) → Incorrect
- \( \text{Option #4: } f(x)=-5\cdot7^x+3 \) → Incorrect
None of the options match the final transformed function \( f(x) = -\frac{7x}{5} - 3 \).
It appears that the correct transformation is not represented accurately in the given options.